Gene Ontology Analysis for Drug Targets of the Whole Genome Transcriptome of Human Vascular Endothelial Cells in Response to Proinflammatory IL-1 - Skaria, Tom; Bachli, Esther; Schoedon, Gabriele (Frontiers in Pharmacology, 2019)
Modulation of proinflammatory responses induced by IL-1β in human vascular endothelial cells (VEC) to reduce tissue damage is an emerging therapeutic strategy to prevent loss of organ function during local or systemic inflammatory diseases. The pathways and signalling molecules involved in IL-1β-induced vascular endothelial inflammation that could be potential targets for therapeutic modulation remain still poorly addressed. Our study applies a genome-wide differential expression approach to identify candidate genes regulated by IL-1β in primary VEC derived from coronary artery (HCAEC). Genes regulated 2-fold were subjected to GO analysis for potential drug targets. We identified HGF as one of the genes upregulated by IL-1β in HCAEC. Gene ontology analysis mapped HGF to a highly significant barrier-injuring and repair pathway, and to an inflammatory disease biomarker network enriched in IL-1β transcriptome in VEC. Further, IL-1β upregulated the expression of BDKRB2, CTSS, and SERT which are also critically involved in regulating VEC monolayer barrier function and can be targeted by therapeutic drugs. To our knowledge, the expression of CTSS and HGF was not yet reported being regulated by IL-1β in human immunocompetent VEC. These findings stimulate further studies to evaluate the critical roles and benefits of therapeutic targeting of BDKRB2, CTSS, HGF, and SERT with known inhibitors to modulate VEC barrier function, and in consequence, vascular leakage in IL-1β-driven inflammatory diseases.